Von Yucatán über Hindelbank ins Flughafengefängnis: Gedanken zu akademischen Wegen und wissenschaftlichen Veränderungen - Achermann, Christin (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
This article traces an academic career that began with an early interest in ethnology and led to social anthropological research on prisons in Switzerland. It focuses on insights into everyday life in correctional facilities, methodological challenges in accessing the field, and reflections on the author's own role and positionality in research. At the same time, institutional changes in the handling of research projects become apparent, as does the importance of trust and reflexivity in the scientific process. From a practical research perspective, the article reflects on the experiences, dynamics, and areas of tension that arise in research in the prison context. (machine translation)